Influence of Dietary Supplementation of Peppermint (Mentha piperita) and Lemongrass (Cymbopogon citratus) Essential Oils on Health Biomarkers in CrossbredCalves - Sarma, Gautami; Palod, Jyoti; Arya, Anita; Kumar, Shive; Sharma, Sanjay; Sharma, R. K.; Singh, S. K .; Gangwar, Sumit (Indian Journal of Animal Nutrition, 2025)
The present study evaluated the effects of dietary supplementation with Mentha piperita essential oil (MPEO) and Cymbopogon citratus essential oil (CCEO) on the hematological profile, serum biochemical parameters, and blood antioxidant status in crossbred calves. 18 crossbred calves (Sahiwal × Holstein Friesian), aged between two weeks and three months, were allocated into three groups: T0 (control), T1 (MPEO at 0.2% of calf starter), and T2 (CCEO at 0.2% of calf starter). The study was conducted over 90 days, with blood samples collected at monthly intervals: 0, 30th, 60th and 90th day for study of haemato-biochemical parameters while at 45th and 90th day for antioxidant parameters . Hematological analysis showed a significant (P